2015
DOI: 10.1038/ng.3289
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in XPR1 cause primary familial brain calcification associated with altered phosphate export

Abstract: Primary familial brain calcification (PFBC) is a neurological disease characterized by calcium phosphate deposits in the basal ganglia and other brain regions, thus far associated with SLC20A2, PDGFB, or PDGFRB mutations. We identified in multiple PFBC families mutations in XPR1, a gene encoding a retroviral receptor with phosphate export function. These mutations alter phosphate export, providing a direct evidence of an impact of XPR1 and phosphate homeostasis in PFBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
215
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 255 publications
(222 citation statements)
references
References 28 publications
4
215
0
3
Order By: Relevance
“…Inorganic phosphate transport is crucial to cellular calcium and phosphate homeostasis and the impairment in the function of PiT2 [17] can contribute to the deposition of calcium phosphate in the vascular extracellular matrix [18]. Although calcification is limited to brain in cases reported with SLC20A2, its role of in homeostasis for inorganic phosphate is evident in several other tissues around the body including bone, parathyroid, and kidneys [19,20].…”
Section: Pathophysiology Of Genetically Determined Brain Calcificationmentioning
confidence: 99%
“…Inorganic phosphate transport is crucial to cellular calcium and phosphate homeostasis and the impairment in the function of PiT2 [17] can contribute to the deposition of calcium phosphate in the vascular extracellular matrix [18]. Although calcification is limited to brain in cases reported with SLC20A2, its role of in homeostasis for inorganic phosphate is evident in several other tissues around the body including bone, parathyroid, and kidneys [19,20].…”
Section: Pathophysiology Of Genetically Determined Brain Calcificationmentioning
confidence: 99%
“…(Figure 1), originally identified as the Xenotropic and Polytropic Retrovirus Receptor 1, which is localised on the surface of many cell types [30]. While an initial overexpression study suggested that the SPX domain is not required for Xpr1's phosphate export function [16], a recent human genetic study revealed that several mutations localised within the SPX domain of Xpr1 are responsible for primary familial brain calcification (PFBC), a disease characterized by calcium phosphate deposits in the basal ganglia [33,34]. Biochemical analysis of SPX-mutated Xpr1 proteins revealed that these mutations do reduce phosphate export, demonstrating a regulatory role for the SPX domain in controlling phosphate efflux activity.…”
Section: The Association Between Spx Domains and Phosphate Metabolismmentioning
confidence: 99%
“…Phosphate overload induces vascular calcification via phenotypic change of vascular smooth muscle cells into osteoblast-like cells, apoptosis of vascular smooth muscle cells, degradation of extracellular matrix in the arterial wall, and release of matrix vesicles. [31][32][33] Furthermore, clinical studies indicated that deposition of vascular calcification in the artery in a spotty pattern enhanced wall stress and promoted wall rupture. 34 These results collectively suggest that high phosphate-induced small-vessel calcification in the brain may lead to rupture of the vessels after exposure to a multitude of arteriosclerotic risk factors in the uremic milieu.…”
Section: September 2016mentioning
confidence: 99%